Revitalization of Production Area and Management Improvements pada UMKM Sopo Nyongko di Kecamatan Sumbersari Kabupaten Jember: Pengabdian - Ardhitya Alam Wiguna; Aditya Nizar Al Ardi; Financia Mayasari; Dicky Andriyanto; Aditya Wahyu Pratama; Reynaldi Akbar Ali (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program aims to revitalize the production area and improve management practices at Sopo Nyongko MSME, a local culinary business in Sumbersari District, Jember Regency. The main problems identified include a limited customer waiting area, non-hygienic and inefficient production processes, traditional packaging methods, and the absence of proper financial records. The implemented solutions consist of expanding the customer waiting space, introducing a cup sealer machine for efficient and hygienic beverage packaging, providing training on Good Manufacturing Practices (GMP) for small-scale food industries, and assisting in financial record-keeping and report preparation based on Micro Business Financial Accounting Standards (SAK-EMKM). The program also introduced digital marketing strategies to enhance market visibility. The results show significant improvements in production efficiency, product hygiene, customer comfort, and financial management capability. Additionally, the implementation of GMP principles supports future halal certification processes. This activity demonstrates that the integration of technology, financial literacy, and digital marketing can increase productivity, business competitiveness, and sustainability for local MSMEs.